Republic of Moldova : Selected Issues. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper highlights the case of Moldova including public investment, efficiency, and growth. The scale up of public investment in Moldova should account for absorption capacity constraints and high reliance on external financing, to ensure a positive impact on growth. It should also be accompanied by efforts to build capacity and strengthen institutions. Public investment in Moldova relies significantly on external loans and grants to finance capital spending. The share of foreign financing varies across sectors, with agriculture and health relying significantly on donor support and education financed mostly domestically. Critical infrastructure needs in Moldova broadly correspond to the priority sectors identified in the National Development Strategy Moldova 2020: energy, transport, agriculture, health, and education. In general, infrastructure in Moldova ranks better regarding coverage than quality. Moldova has a relatively high index of public investment efficiency; nonetheless there are a number of dimensions to improve investment process.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Moldova, Republic of